What Are The Factors Affecting The Financial Sustainability of Social Enterprises in Egypt? - Ghaly, Mina Atta (AUC Knowledge Fountain, 2026)
This thesis investigates what factors affect the financial sustainability of social enterprises (SEs) in Egypt, situating them within a constrained MSME, legal and sectoral context marked by informality, weak innovation and recurrent shocks. Drawing on global and Egyptian literature, it identifies ten candidate factors—business model, financial management, founders’ skills and mindset, revenue structure, sector and mission, legal framework and innovative finance, capacity building, investment mechanisms and “the right investor”, adaptability to shocks, and ecosystem conditions—and integrates them into an extended Social Enterprise Model Canvas. Using a qualitative, exploratory design with semi‑structured interviews of social enterprise founders, incubators/accelerators, investors and experts, the study employs inductive thematic analysis to derive ten overarching themes. The most salient relates to having a solid, profit‑oriented business model, robust financial‑management systems, relevant and sustained capacity building, alignment with investors who understand hybrid models, the ability to adapt to economic and policy shocks, and the enabling or constraining role of the wider ecosystem, alongside cross‑cutting insights on investor perceptions of SEs and mission–profit tensions. The thesis offers practical recommendations for policymakers and support organisations and contributes to the literature as one of the first multi‑factor, Egypt‑focused analyses of social enterprise financial sustainability that explicitly incorporates shock‑adaptation, investor perceptions and the quality of capacity‑building support.